Prayers and Bhajans in the Mandap of the Maruti Temple - Mumbai Archive Project Team (Jio Institute, 2024)
The inner sanctum (garbagriha) inside the Maruti Temple is made from stone, with a circumambulatory path going around it. In front of the garbagriha is a spacious mandap used for prayers and congregations. Devotees gather here to chant the Hanuman Chalisa and sing bhajans.